Fuel effects on aqueous film formation and foam degradation and their impact on fire suppression by foams containing fluorosurfactants. (24th September 2020) - Hinnant, Katherine; Button, Michael; Giles, Spencer; Snow, Arthur; Ananth, Ramagopal
Summary: Spreading coefficient, foam degradation, fuel transport through a foam layer, foam spread, and fire extinction time were collected by varying fuels for a given fluorosurfactant formulation. Varying fuel structure systematically enabled variation of foam‐fuel interactions, and spreading coefficients, which affected aqueous film formation. A wide range of spreading coefficients were studied using two foam formulations. Surfactant formulations with near‐zero or negative spreading coefficients (−1.2, −0.12 mN/m) suppressed the fires within the same time or faster than those with positive spreading coefficients (1.77, 3.28 mN/m). Both foams extinguished an iso‐octane and methylcyclohexane pool fire despite negative spreading coefficients on iso‐octane and positive spreading coefficients on methylcyclohexane. The fire extinction times collected relate more closely to foam degradation than to film formation. Foam degradation results showed a roughly 20% variation in lifetime between the two foams and the three fuels, consistent with fire extinction times. To understand the relationship between foam degradation and solution properties, a single lamella experiment was designed that monitors lamella thickness and lifetime. This experiment, relating solution to foam properties, will aid in the development of environmentally friendly surfactant replacements in firefighting foams.